Figure 2 from: Heron J, Sheffield C (2016) First Canadian record of the water mite Thermacarus nevadensis Marshall, 1928 (Arachnida: Acariformes: Hydrachnidiae: Thermacaridae) from hot springs in British Columbia. Biodiversity Data Journal 4: e9550. https://doi.org/10.3897/BDJ.4.e9550 - Heron, Jennifer; Sheffield, Cory (Zenodo, 2016)
Figure 2 - The public hot spring at Alpha Pool in Liard River Hot Springs Provincial Park in northeastern British Columbia. Mites were collected on the undeveloped border of the pool to the left of the photo. Photo by C. Sheffield.